Ischemic Stroke and its Correlation with Low Blood Cholesterol Levels: Ischemic Stroke and Low Cholesterol Levels - Rafique, Saima; Rind Baloch, Muhammad Aslam; Nazir, Maria; Saleem, Muhammad (Pakistan Journal of Health Sciences, 2023)
Ischemic stroke occurs as a result of blockage of blood supply to the brain. It causes damage of brain tissue due to less availability of oxygen and nutrients. HDL-C is a significant risk factor for ischemic stroke. Objective: To evaluate the low HDL-C levels in ischemic stroke hospitalized patients. Methods: It is a descriptive cross sectional retrospective study conducted at Liaquat University Hospital, Hyderabad, Pakistan. The anticipated association of abnormal HDL-C levels in ischemic stroke was assessed in 200 cases. The data were collected from hospital records, patients were confirmed for stroke on the basis of CT scan. This descriptive analysis was performed based on the lab findings of patients from hospital records. Medical history, CT scans and demographic information of patients was obtained from hospital records after taking data collection permission from hospital. Results: A low level of HDL-C was identified in 126 patients (64%) according to the study’s results. When the HDL-C values of ischemic stroke patients were compared using the Chi-Square Test, the p value obtained was 0.0001. Conclusions: The majority of ischemic stroke patients had low serum HDL-C levels. This study suggests an association of low serum HDL-C levels with susceptibility or risk for ischemic stroke.<span class="EOP SCXW198576196 BCX0" data-ccp-props=""134233117":false,"134233118":false,"134245417":true,"134245418":false,"134245529":false,"201341983":0,"335551550":6,"335551620":6,"335559740":240,"335559795":0">